Latihan Shuttle Run untuk Meningkatkan Kecepatan Reaksi Atlet Taekwondo - Yusfi, Herri; Ambarwati, Evayulia; Destriana, Destriana; Destriani, Destriani (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2024)
This research aimed to determine the effect of shuttle run training on increasing the reaction speed of Ogan Ilir taekwondo athletes. The type of research used in this research is quasi-experimental, using a one-group pretest and posttest design. This design uses a pretest (before treatment) so that the treatment results can be known more accurately because it compares with the situation before treatment. This research used a sample of 30 female Ogan Ilir taekwondo athletes. The research instrument was Whole Body Reaction with data analysis tests using SPSS version 26 with the T-score test. The findings of this research are that shuttle run training can increase reaction speed. The conclusion from this research is that shuttle run training can increase taekwondo athletes' reaction speed. Keywords: Reaction Speed, Shuttle Run, Taekwondo.